Penentuan Lokasi TPA dengan Pendekatan Spasial di Pulau Kecil Kota Makassar - Birawida, Agus Bintara; Makkau, Bukroanah Amir; Dwinata, Indra (Media Kesehatan Masyarakat Indonesia, 2018)
Solid waste is an environmental issue that currently still occurs in the islands, especially for small islands. Every year waste disposed into the sea continues to experience levels caused by community activities around the island. The aimof the research is to determine the best point in the location of the Final Waste Disposal Site (TPA). This research uses descriptive method with spatial approach. Retrieval of data to determine locations in GPS location and measurement in the field. The results showed that the GPS coordinate points and the objectives of the measurement purposes, namely the slope of the slope, the distance between the coast and land, the land function, including the air of the ground, and the capacity of the available land for locations on Kodingareng Lompo Island latitude 119.26514o and longitude of -5.14793o placed in the center of the island. Sanitary landfill is the most suitable type of landfill to be applied on Kodingareng Lompo Island.